Implementasi Modul Ajar Dalam Pembelajaran Sejarah Di Era Kurikulum Merdeka Pada Kelas X SMA Negeri 2 Banjarmasin - Halda Nor Halisa; Ersis Warmansyah Abbas; Syaharuddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The independent curriculum is one part of the learning recovery effort where teachers use teaching modules as a learning design aimed at delivering content to students systematically. This research aims to analyze the implementation of teaching modules by history teachers in class X SMAN 2 Banjarmasin, this research uses descriptive qualitative methods. Data collection techniques through observation, interviews and document analysis. Data analysis techniques use data collection, data reduction, data presentation, as well as drawing conclusions and verification. Data validity techniques use triangulation of techniques and sources. Based on the results of the analysis carried out, the implementation of teaching modules by history teachers in class The school will not let this problem drag on. To overcome these problems so that teaching and learning activities are not hampered and can help teachers implement teaching modules, the efforts made are the implementation of learning communities in schools and workshop activities to increase teacher competence so that teachers in learning can improve the quality of competence in teaching.